Strengthening the Strategic Role of BUMDes through Inclusive Partnerships and the Pentahelix Approach to Encourage Sustainable Village Economy in Kampar Regency - Abshor Marantika; Librina Tria Putri; Maulina Agustiningsih; Suarni Norawati; Husein Husein; Dwika Lodia Putri (Jurnal Pengabdian Pancasila (JPP), 2025)
The community service program aimed at BUMDes managers in Kampar Regency has brought significant results. The managerial training provided has strengthened the managers' abilities in business planning and financial management, resulting in more transparent reports and data-based decisions. In addition, the strategic partnerships and marketing strategies introduced have expanded market access for BUMDes products, increasing visibility and sales in regional and national markets. The program has succeeded in strengthening the synergy between BUMDes and various stakeholders, including local governments, business actors, and academics, which has created an environment that is more supportive of BUMDes growth. Simplification of regulations and bureaucracy reduces administrative barriers for BUMDes, strengthening support and ensuring the long-term sustainability and success of BUMDes in Kampar Regency.